ANALISIS TENTANG PERANAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PELAJARAN IPS DI KELAS VIII SMP SWASTA KRISTEN BNKP TELUK DALAM - Laia, Rohani (Universitas Nias Raya, 2025)
This research is motivated by student activity and student learning motivation which tends to be low. The purpose of this research is to 1) Describe the role of teachers in increasing students' learning motivation in social studies lessons in class VIII of BNKP Teluk Dalam Christian Private Middle School. 2) Describe students' learning motivation in social studies lessons in class VIII of BNKP Teluk Dalam Christian Private Middle School. Type of qualitative research. The data sources used are primary and secondary data. Data collection techniques through interviews, observation, documentation. Research results and conclusions: 1) The role of teachers in increasing students' learning motivation is giving praise, providing understanding for good learning, forming good study habits, helping children with learning difficulties, using varied methods, and using learning media. 2) Students who have motivation to learn, study regularly, make a study schedule, have the desire to succeed in studying, are enthusiastic about learning, and complete their study assignments well. Students who have low learning motivation: study irregularly, are less active in learning, have low curiosity, and do not have the courage to ask and answer questions given by the teacher. Suggestions 1) For students, they should understand study time and play time and be active in learning activities and always pay attention and listen to the teacher during lessons so they understand what the teacher is teaching. 2) Teachers should pay more attention to each student's difficulties because each student definitely has different understanding and learning problems. 3) Parents of students should give full attention to their children in learning by encouraging, guiding and helping overcome learning difficulties experienced by students.